Implementasi dan Pengujian Efektivitas Metode Extreme Programming dalam Pengembangan Aplikasi Web Manajemen Persuratan pada Lembaga MPR RI - Dafa Adi Raharjo; Budi Apriyanto (CV. Multi Kreasi Media, 2026)
This study focuses on the implementation and effectiveness testing of the Extreme Programming (XP) method in the development of a web-based letter management application for the MPR RI institution. Currently, the institution's correspondence process is still carried out in a conventional-semi digital manner, which often leads to obstacles such as inefficiency, delays, and difficulties in document tracking. Therefore, the main objective of this research is to design and build a web-based system that can address these issues, thereby improving the efficiency and transparency of correspondence management. The Extreme Programming (XP) method was chosen for its adaptive and quality-oriented approach, where user feedback is a key element in every stage of development. The results of this study indicate that the application of XP successfully produced a functional and effective application for managing correspondence and was able to enhance work productivity within the MPR RI environment.